Facilitating psychotherapy with patient-made videos: A qualitative study of patient experiences - Nordström Elisa; Luutonen Sinikka; Paananen Jenny; Koffert Tarja; Keinänen Matti; Hietala Jarmo (European Association for Integrative Psychotherapy, 2022)
We have developed a method utilizing video material to facilitate the psychotherapeutic process we call VideoTalk. In this method, which uses schema therapy as a theoretical framework, patients make videos at home in various emotional situations following the therapist’s detailed instructions. They then watch the videos together with the therapist making observations about the patient and how they speak about themselves and other people. The aim of this article is to describe five patients’ personal experiences of psychotherapy consisting of 15 video-assisted sessions. We used mixed methods methodology consisting of material-based content analysis of patient interviews done after the therapy and changes in symptoms measured by psychological symptom scales. Based on the symptom scales, this outcome study found that all participants benefited from the VideoTalk therapy. ‘Gaining bodily self-awareness and insight’, ‘Thinking more clearly and with self-compassion’, and ‘Challenges associated with the technology and practicalities of video work’ were found to be the main categories in the content analysis. After some minor technical difficulties, the patients found the video method workable. The results showed a wide range of self-observations, which began to be positively integrated into the patients’ lives and to increase their overall wellbeing. In the course of VideoTalk therapy, patients face painful emotions and may begin to create a new kind of connection between their own insulated internal world and the surrounding world.